High-CPAP Does Not Impede Cardiovascular Changes at Birth in Preterm Sheep - Tessa Martherus; Kelly J. Crossley; Karyn A. Rodgers; Janneke Dekker; Janneke Dekker; Anja Demel; Alison M. Moxham; Valerie A. Zahra; Graeme R. Polglase; Graeme R. Polglase; Calum T. Roberts; Calum T. Roberts; et al. (Frontiers Media S.A., 2021)
Objective: Continuous positive airway pressures (CPAP) used to assist preterm infants at birth are limited to 4-8 cmH2O due to concerns that high-CPAP may cause pulmonary overexpansion and adversely affect the cardiovascular system. We investigated the effects of high-CPAP on pulmonary (PBF) and cerebral (CBF) blood flows and jugular vein pressure (JVP) after birth in preterm lambs.Methods: Preterm lambs instrumented with flow probes and catheters were delivered at 133/146 days gestation. Lambs received low-CPAP (LCPAP: 5 cmH2O), high-CPAP (HCPAP: 15 cmH2O) or dynamic HCPAP (15 decreasing to 8 cmH2O at ~2 cmH2O/min) for up to 30 min after birth.Results: Mean PBF was lower in the LCPAP [median (Q1-Q3); 202 (48-277) mL/min, p = 0.002] compared to HCPAP [315 (221-365) mL/min] and dynamic HCPAP [327 (269-376) mL/min] lambs. CBF was similar in LCPAP [65 (37-78) mL/min], HCPAP [73 (41-106) mL/min], and dynamic HCPAP [66 (52-81) mL/min, p = 0.174] lambs. JVP was similar at CPAPs of 5 [8.0 (5.1-12.4) mmHg], 8 [9.4 (5.3-13.4) mmHg], and 15 cmH2O [8.6 (6.9-10.5) mmHg, p = 0.909]. Heart rate was lower in the LCPAP [134 (101-174) bpm; p = 0.028] compared to the HCPAP [173 (139-205)] and dynamic HCPAP [188 (161-207) bpm] groups. Ventilation or additional caffeine was required in 5/6 LCPAP, 1/6 HCPAP, and 5/7 dynamic HCPAP lambs (p = 0.082), whereas 3/6 LCPAP, but no HCPAP lambs required intubation (p = 0.041), and 1/6 LCPAP, but no HCPAP lambs developed a pneumothorax (p = 0.632).Conclusion: High-CPAP did not impede the increase in PBF at birth and supported preterm lambs without affecting CBF and JVP.